The role of lncRNA-mediated pyroptosis in cardiovascular diseases - Hu, Bo; Chen, Wen; Zhong, Yancheng; Tuo, Qinhui (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular disease (CVD) is the leading cause of death worldwide. Pyroptosis is a unique kind of programmed cell death that varies from apoptosis and necrosis morphologically, mechanistically, and pathophysiologically. Long non-coding RNAs (LncRNAs) are thought to be promising biomarkers and therapeutic targets for the diagnosis and treatment of a variety of diseases, including cardiovascular disease. Recent research has demonstrated that lncRNA-mediated pyroptosis has significance in CVD and that pyroptosis-related lncRNAs may be potential targets for the prevention and treatment of specific CVDs such as diabetic cardiomyopathy (DCM), atherosclerosis (AS), and myocardial infarction (MI). In this paper, we collected previous research on lncRNA-mediated pyroptosis and investigated its pathophysiological significance in several cardiovascular illnesses. Interestingly, certain cardiovascular disease models and therapeutic medications are also under the control of lncRNa-mediated pyroptosis regulation, which may aid in the identification of new diagnostic and therapy targets. The discovery of pyroptosis-related lncRNAs is critical for understanding the etiology of CVD and may lead to novel targets and strategies for prevention and therapy.